Too Many People Left Behind: The Crucial Importance of TVET - Hazelkorn, Ellen (International Higher Education, 2021)
Have we given as much attention to people who do not attend college and university as to those who do? Assumptions that massification would, on its own, provide opportunities for everyone are being heavily questioned. Technical and vocational education and training colleges and polytechnics are increasingly acknowledged as playing an indispensable role in post-18 years’ education. Many countries are going further—reframing policy discussion around tertiary education, inclusive of formal, nonformal, “second-chance,” and life-long learning.